Chinese Immigrant Parenting Style and Its Effect on the Main Character’s Psychological Condition Reflected in Turning Red (2022) - Fatiha Zaidatus Salsabila; Christina Christina (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study is aimed to analyze : (1) Chinese immigrant parenting style in U.S.A towards main character’s psychological condition reflected in Turning Red (2022), (2) the effect of parenting style on the main character’s emotion and behavior is presented in Turning Red (2022). The study uses descriptive qualitative method to analyzed the film entitled Turning Red (2022) directed by Domee Shi as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by used exposing, explaining, and interpreting. The researcher analyzes the data by uses psychology of literature and parenting style approach in doing the process of the research. The result of the study: the parenting style of Chinese immigrant in U.S.A element within this research. They are firstly, psychological condition which belongs to main character is dominate with the id. It means that the id, ego, and superego are not balanced. Secondly, the effect of parenting style clearly describe on the main character which are convey their emotions in the wrong way, are not good at making decisions, lack self-confidence, and often compare themselves with other people.